Institutionalizing gender equality urban development experience of the Bangladesh local government engineering department. (Asian Development Bank, 2017)
ADB supports the institutionalization of gender equality in government agencies to enhance their gender-responsiveness and sustainability of gender equality results. The Bangladesh Local Government Engineering Department (LGED) is a trailblazer in mainstreaming gender equality in its policies, systems, and programs. This has resulted in womens greater benefit from ADB assisted projects and in their increased participation in decision making for inclusive urban development. This report presents the results of a stocktaking of LGEDs gender mainstreaming practices particularly in ADB financed urban development projects. Find out more about the lessons identified and recommendations offered to enhance LGEDs approaches to achieving gender equality and womens empowerment in Bangladesh.